2021
DOI: 10.1111/1750-3841.15947
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the di‐ and tri‐chlorinated haloacetic acids during broiler prechilling

Abstract: Sodium hypochlorite (NaClO) has been widely used at 100 ppm concentration during poultry slaughter to reduce carcass microorganism loads. However, its use in poultry processing is restricted owing to the potential risks of disinfection by-products (DBPs) that can be produced by the reaction of NaClO with poultry meat components. This study assessed whether dichloroacetic acid (DCAA) and trichloroacetic acid (TCAA), as primary DBP representatives, were produced when NaClO was used as a disinfectant in various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Currently, NaOCl is mainly used as a chlorine-based disinfectant in poultry farms. Due to its poor persistence as a consequence of its high volatility, NaOCl is used to disinfect drinking water and slaughtered chickens [ 27 ]. While it is regarded to have a strong virucidal activity, there are some disadvantages which are noted above in the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, NaOCl is mainly used as a chlorine-based disinfectant in poultry farms. Due to its poor persistence as a consequence of its high volatility, NaOCl is used to disinfect drinking water and slaughtered chickens [ 27 ]. While it is regarded to have a strong virucidal activity, there are some disadvantages which are noted above in the introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although more studies are required to evaluate the textural changes found in the chicken breast that had NaClO added, it has been reported that chicken meat with added NaClO during broiler pre-chilling reacts with the meat, producing dichloroacetic acid (DCAA) and tricholoacetic acid (TCAA)-reactions that are precursors found in chicken and water (carbohydrates, lipids, proteins, etc.) [80], which are macronutrients responsible for the texture of the meat. These types of reactions could contribute to changes in texture.…”
Section: Texturementioning
confidence: 99%
“…acid (DCAA) and tricholoacetic acid (TCAA)--reactions that are precursors found in chicken and water (carbohydrates, lipids, proteins, etc.) [80], which are macronutrients responsible for the texture of the meat. These types of reactions could contribute to changes in texture.…”
Section: Texturementioning
confidence: 99%